OP0020 Validation of gene signatures to predict rheumatoid arthritis development. (23rd January 2014) - Lubbers, J.; Brink, M.; van de Stadt, L.A.; Vosslamber, S.; Wesseling, J.G.; van Schaardenburg, D.; Rantapaa-Dahlqvist, S.M.; Verweij, C.L.
Abstract : Background: Early recognition of development of rheumatoid arthritis (RA) allows timely start of treatment. It is known that antibodies against citrullinated proteins (ACPA) and rheumatoid factor (RF) have a predictive value for development of RA within 5 years. Since only 20-40% of ACPA + and/or RF + seropositive arthralgia patients develop arthritis, better prognostic markers are required. Recently, we reported gene signatures in the peripheral blood (PB), involving interferon (IFN) response gene activity and B-cell related genes, which are associated with the development of arthritis. Objectives: The objective of this study is to validate the signatures of IFN response gene activity and B-cell related genes in independent cohorts. Methods: PB samples of an independent group of 40 seropositive arthralgia patients from the Amsterdam Reade cohort who are clinically followed for arthritis development were analyzed for their IFN-response gene activity, defined as a score based on the average expression of 7 IFN-response genes. In addition PB mononuclear cells (MCs) of 22 pre-onset RA, 25 RA patients and 48 population based controls (PC) from the Medical Biobank of Northern Sweden (Umeå) were studied. FACS-analysis for B-cell markers expression was performed on PB from 87 seropositive arthralgia patients and 30 healthy controls (HC) from the Amsterdam Reade cohort. qPCR for B-cell markers expression was performed in 45 seropositive arthralgia patients and 6 HC from the Amsterdam Reade cohort. Results: Of the 40 seropositive arthralgia patients analyzed for INF-scores, 19 developed arthritis within a median period of 11 months (IQR 9-28). Comparative analysis of INF-score high and low patients confirmed that an increased IFN-score is associated with conversion to arthritis (p=0.025). In addition, the IFN-score was measured in PBMC from RA, pre-onset RA patients and PC from the Medical Biobank of Northern Sweden. Comparative analyses between the groups revealed that both pre-onset RA patients as well as RA patients had significantly increased IFN-scores compared to HC (Mann-Whitney U test p=0.006 and p=0.008, respectively). Of the 87 seropositive arthralgia patients analyzed for B-cell marker expression, 22 developed arthritis within a median period to conversion of 11 months (IQR 5-13). Low B-cell markers expression was significantly associated with conversion to arthritis (p=0.01). An interim analysis with qPCR showed a strong trend towards decreased B-cell transcript markers and arthritis conversion (p=0.07). Conclusions: These results provide evidence for the validation for a role of IFN-activity and low B-cell presence in the preclinical phase of RA. Further studies are aimed to demonstrate the diagnostic value of these markers. Acknowledgements: This research was supported by the Center for Translational Molecular Medicine (CTMM) consortium "TRACER". Disclosure of Interest: None Declared